2011
DOI: 10.1016/j.ajpath.2011.01.036
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylcysteine Amide (NACA) Prevents Retinal Degeneration by Up-Regulating Reduced Glutathione Production and Reversing Lipid Peroxidation

Abstract: Oxidative stress plays a critical role in accelerating retinal pigment epithelial dysfunction and death in degenerative retinal diseases, including age-related macular degeneration. Given the key role of oxidative stress-induced retinal pigment epithelial cell death and secondary photoreceptor loss in the pathogenesis of age-related macular degeneration, we hypothesized that a novel thiol antioxidant, N-acetylcysteine amide (NACA), might ameliorate cellular damage and subsequent loss of vision. Treatment of hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 65 publications
1
47
0
3
Order By: Relevance
“…Given the strong association between neuroinflammation and glaucomatous optic neuropathy (7), we performed a retinal cytokine/growth factor-focused PCR array consisting of 88 genes (ILs, TNF and TGF superfamilies, growth factors, interferons, chemokines, and others) to identify factors whose expression correlates specifically with RGC death. In order to identify factors unique to RGC death, we used 3 different murine models of disease: optic nerve crush (ONC) as a model of axonal injury and RGC-specific death as seen in glaucoma, light-induced retinal degeneration (RD) as a model of photoreceptor-specific cell death, and endotoxin-induced uveitis (EIU) as a model of ocular inflammation (8)(9)(10). By comparing the retinal gene expression profiles associated with these 3 murine models of disease and focusing specifically on factors that are uniquely identified in the ONC model but not the RD and EIU models, we could identify the factors that were uniquely associated with RGC death.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the strong association between neuroinflammation and glaucomatous optic neuropathy (7), we performed a retinal cytokine/growth factor-focused PCR array consisting of 88 genes (ILs, TNF and TGF superfamilies, growth factors, interferons, chemokines, and others) to identify factors whose expression correlates specifically with RGC death. In order to identify factors unique to RGC death, we used 3 different murine models of disease: optic nerve crush (ONC) as a model of axonal injury and RGC-specific death as seen in glaucoma, light-induced retinal degeneration (RD) as a model of photoreceptor-specific cell death, and endotoxin-induced uveitis (EIU) as a model of ocular inflammation (8)(9)(10). By comparing the retinal gene expression profiles associated with these 3 murine models of disease and focusing specifically on factors that are uniquely identified in the ONC model but not the RD and EIU models, we could identify the factors that were uniquely associated with RGC death.…”
Section: Resultsmentioning
confidence: 99%
“…Light exposure to induce RD was performed as previously described (9). Briefly, 6-week-old 129S1/SvImJ mice were dark adapted overnight.…”
Section: Methodsmentioning
confidence: 99%
“…12,[26][27][28] Our results are in agreement with previous studies which reported an increase in GSH levels after NACA incubation and a decrease in GSH levels upon TBHP treatment in an ARPE cell line. 11,14 Importantly, changes in the GR activity were also observed. GR regenerates GSH from GSSG and plays an important role in GSH homeostasis.…”
Section: Discussionmentioning
confidence: 87%
“…In an animal model, phototoxicity-induced photoreceptor cell death and photoreceptor dysfunction were prevented by NACA. 14 The experiments reported here utilized primary cultures of human retinal pigment epithelial cells (HRPEpiC), the best available in vitro model for studying RPE-related disorders. Because we attempted to mimic a human disease and provide a solution using a "disease-in-the-dish" model, choosing the most representative cell model was critical.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation